Job placement via private vs. public employment agencies: Investigating selection effects and job match quality in Germany - Adam Ayaita; Christian Grund; Lisa Pütz (Schmalenbach Journal of Business Research (SBUR), 2022)
Employment agencies aim to match individuals to appropriate jobs. There are public and private employment agencies, which co-exist in many countries. Selection effects may be relevant in the sense that private agencies potentially engage in 'cream-skimming' by prioritizing highly qualified workers. The resulting job match quality is also important from an individual, a~firm, and a~society perspective. We examine the selection into job placement via private and public employment agencies as well as the resulting job match qualities, taking a~job-market reform in Germany into account: the introduction of vouchers for private job placements. Using representative German panel data, we find that cream-skimming is significantly less pronounced under the voucher policy, as private agencies shift the focus toward unemployed individuals with a~voucher. In addition, we find evidence based on propensity score matching estimations that private agencies tend to create better matches than their public counterparts.
Keywords: 650; Cream-skimming; Employment agencies; Job match quality; Job placement; Job search; Vouchers